PkM Mendorong Peningkatan Ekspor Produk Unggulan Daerah Kabupaten Indragiri Hilir (Kelapa) melalui Pemanfaatan Digital Marketing pada UMKM - Khairul Ihwan; Bayu Fajar Susanto; Roberta Zulfhi Surya; Najamuddin; Ridwan, Muannif; Badewin (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2025)
This Community Service Program (PkM) focuses on increasing exports of superior regional products in Indragiri Hilir Regency, namely coconut, through the use of digital marketing for Micro, Small and Medium Enterprises (MSMEs). MSMEs in this area, such as Gudang Kelapa Doa Ibu, face challenges in marketing their products globally due to limited knowledge and access to technology. This program is designed to empower MSMEs with training and assistance in using digital marketing strategies, including social media, websites and e-commerce. The service team also helps develop digital platforms such as e-commerce websites, inventory management applications, and integrated digital marketing systems that are tailored to the needs of MSMEs. The main objective of this program is to expand the export market, increase sales volume, and strengthen the position of coconut products from Indragiri Hilir Regency on the international market. This program also targets increasing human resource capacity in digital marketing and contributing to regional economic growth. The evaluation results show increased product visibility online, increased export sales, and strengthened the capacity of MSMEs in adopting digital technology for marketing and business operations.